Molecular Characterization And Phylogenetic Analysis Of Hepatitis C Virus (HCV) Genotype 3a In Swat District, Pakistan - Mohammad Nasar; Saqib Mumtaz; Muhammad Nadeem Hassan; Ijaz Ali; Hamid Ali; Sagar M. Goyal (Kurdish Studies, 2023)
Introduction: The clinical manifestations of infection with hepatitis C virus (HCV) range from acute hepatitis to chronic liver diseases including liver cirrhosis and hepatocellular carcinoma. HCV genotyping is vital for understanding pathogenesis and developing treatment plans. Methods: A total of 664 blood samples from patients referred for liver function tests (LFT) were collected from four diagnostic laboratories in Swat District, Pakistan. Results: Of the 664 blood samples, 327 (49.25) had serum glutamic-pyruvic transaminase (SGPT) levels of more than 50U/L. These samples were analyzed for HCV antibodies using immuno-chromatography (ICT). ICT-positive sera were further tested for HCV RNA by PCR, and results revealed that 43 of the 282 ICT-positive samples (15.25%) were positive for HCV RNA. Three out of the 43 HCV RNA-positive samples were sent for sequencing for the NS5B region. All three HCV strains were classified into genotype 3 and sub genotype 3a. Conclusion: These findings are indispensable in informing healthcare providers of the prevalence of HCV genotypes in Swat district and thus contributing to better management of the infection through the development of better treatment plans. The findings are also important to develop health-related policies with the aim of overcoming the burden of HCV in the country.